Temperature-dependent crack induced by microstructure evolution in 20Mn2SiMoCuV bainite wheel steel. (October 2022) - Liu, Yanru; Tan, Zhunli; Tian, Yu; Zhu, Jiaqi; Zhang, Min; Zhang, Mingru; Zhao, Hai
Highlights: Repeated temperature variations occurred between wheel tread and brake shoe. Adverse microstructure evolutions were brought by the variations. Retained austenite decomposed and cementite precipitated leading to cracks' creation. Abstract: Several severe cracks were found in novel 20Mn2SiMoCuV bainite wheel tread after 100, 000 km test running, which will significantly affect bainite wheel's service safety. The reason for cracks generation was investigated through microstructure observation and wheel/shoe contact analysis. Results showed that cracks were caused by microstructure evolutions resulting from temperature variations during quickly heating and cooling repeatedly in braking at contact interface of wheel tread and brake shoe. Temperature increased to above 500 °C at contact area will reduce the bainite wheel microstructure stability, leading to retained austenite decomposition to brittle martensite and cementite precipitation along grain boundary and lath boundary. Both above brittle martensite and cementite provided location for crack initiation and propagation. Therefore, some measures can be suggested to prevent initiation and propagation of cracks such as optimizing heat treatment process parameters to improve microstructure stability and adjusting matching of wheel tread/brake shoe to coordinate thermal conductivity.